HUBUNGAN SELF-EFFICACY DOSEN DENGAN SELF-EFFICACY MAHASISWA YANG SEDANG MENYUSUN SKRIPSI DI SEMESTER GANJIL 2015/2016 UNIVERSITAS SULTAN AGENG TIRTAYASA - Damanhuri Damanhuri; Lukman Nulhakim; Mukhtar Mukhtar (JPSD (Jurnal Pendidikan Sekolah Dasar), 2016)
Abstrak. Penelitian ini bertujuan untuk mengetahui 1) tingkat self-efficacy dosen yang sesang membimbing skripsi mahasiswa di semester ganjil 2015/2016, FKIP Untirta, 2) tingkat self-efficacy mahasiswa yang sedang menyusun skripsi di semester ganjil 2015/2016 FKIP Untirta, 3) hubungan self-efficacy dosen dalam membimbing skripsi mahasiswa dan self-efficacy mahasiswa dalam menyusun skripsi di semester ganjil 2015/2016, FKIP Untirta. Penelitian ini menggunakan metode deskriptif dengan penggujian korelasi. Subjek penelitian adalah dosen dan mahasiswa yang sedang membimbing dan menyusun skripsi. Instrument penelitian berupa angket. Hasil penelitian menunjukkan bahwa terdapat hubungan self-efficacy antara dosen dan mahasiswa yang sedang menyusun skripsi pada semester ganjil 2015/2016. Kata Kunci: Self Efficacy mahasiswa dan dosen   Abstact. Thesis is a task which is composed of students as evidence of learning for undergraduate education. in the process of preparation of the thesis students will encounter obstacles different and beliefs that can vary to deal. this will affect the time required to complete the thesis, these problems, researchers wanted to test relationship with self-efficacy lecture and students are in compiling thesis odd semester 2015/2016, faculty of teacher training and pedagogical, university of sultan ageng tirtayasa. the aim of research was to find out whether there relationship with self-efficacy lecture and students are in compiling thesis odd semester 2015/2016, faculty of teacher training and pedagogical, university of sultan ageng tirtayasa. This type of research used in this research is the survey method. This study is correlations, samples are student and lecture faculty of teacher training and pedagogical, university of sultan ageng tirtayasa. The result of research could be concluded as follows: (1) there is relational relationship with self-efficacy lecture and students are in compiling thesis odd semester 2015/2016, faculty of teacher training and pedagogical, university of sultan ageng tirtayasa.                                                                                Key Word: Self Efficacy, Studen and Lecture